The Explanation of Inflation: Some International Evidence - Brünner, Karl; Meltzer, Allan H. (American Economic Review, 2018)
Explanations of inflation can be subdivided into two major groups. "Sociological theories" assert that movements of prices and wages proceed independently of market conditions. Economic theories on the other hand elaborate the essential dependence of price-wage movements on evolving market conditions. Sociological theories, dominant in Europe, emphasize the role of a wide array of institutional arrangements. In contrast, according to economic theory all forces and events affect inflation via market processes